Antibacterial activities of extracts from different parts of Swietenia mahagoni against multiple-drug resistant bacteria - Tan, Wee Yeong (2012)
This study concerned with the evaluation of antibacterial activity of crude extracts of three parts (leaf, fruit cover, seed cover and seed) of Swietenia mahagoni obtained by three solvents (acetone, ethanol and hexane). The seedoil obtained by solvent continuous extraction method (Soxhiet) from seed by using hexane as solvent. The antibacterial activity of these extracts was assessed against two multiple-drug-resistance bacteria strains namely, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) by the well diffusion method. For the antibacterial bioassay, four concentrations (0.1, 0.2, 0.4 and 0.8%) of each solvent and part extract solutions were prepared; DMSO was used to solubilize the extract in water. A control using 1% dimethyl suldoxide (DMSO) used for comparison. The antibacterial activity among extracts was extremely broad against both test organisms. With higher concentration (0.8%) the acetone extracts from fruit cover and leaf displayed overall more potent activity than other parts against S. aureus; whereas ethanol extracts from fruit and seed cover showed more efficiency against E. coli. However, no inhibition activity of leaf acetone and ethanol against E. coli with concentration of 0.8%. Bioactive groups such as alkaloid and sesquiterpene lactones were screened by Thin Layer Chromatography (TLC); and the results obtained were positive. The experimental results obtained from this study suggest that Swietenia mahagoni extracts are promising as natural antibacterial and this may warrant further research to determine the bioactive compound(s).